El gasto publico improductivo : Un enfoque pragmatico para el analisis de las medidas de politica. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
El gasto publico improductivo.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet